ChemInform Abstract: Modular Isoquinoline Synthesis Using Catalytic Enolate Arylation and in situ Functionalization. Issue 22 (3rd June 2014) - Pilgrim, Ben S.; Gatland, Alice E.; McTernan, Charlie T.; Procopiou, Panayiotis A.; Donohoe, Timothy J.
Abstract A multistep synthesis of functionalized isoquinolines using Pd‐catalyzed reaction of compounds (I), (V), and (XI) with methyl ketones followed by quenching with a variety of electrophiles is developed.